Preparation And Characterization Of Recycled Carbon/Fibercarbon Nanotube Reinforced Epoxy Composites - Law, Mei Lin (UTeM, 2016)
The usage of carbon fiber reinforced polymers (CFRP) has been growing at a substantial rate that leads to the increasing amount of waste generated from end-of-life components and manufacturing scrap. Recognizing the hazardous waste that would be harmful to the human health as well as the environment, this has poses the need to recycle the waste. This report presents the research of compression and wear behaviour of as-received as well as treated rCF and carbon nanotube (CNT) reinforced epoxy composites. The rCF derived from mechanically recycled CFRP composite woven prepreg waste - materials impregnated with epoxy resin is of low value commodity. Therefore, cyclic cryogenic treatment is introduced to produce valuable product of rCF. The objectives of this study were to investigate the effect of cyclic cryogenic treatment on the recycled carbon fiber as well as to study the performance of the as-received rCF reinforced epoxy (EP/rCF-AR), treated rCF reinforced epoxy (EP/rCF-T) and carbon nanotube reinforced treated rCF and epoxy (EP/rCF-T/CNT) composites. The composites’ samples were fabricated using vacuum casting technique. The samples were then subjected to physical, compression and tribological testing. In addition, microscopy examinations were carried out to observe and to analyse the morphology of the worn surfaces. It was found that at 25 cycles of cryogenic treatment, the epoxy resin on the surface of rCF is nearly absent, indicating the effective removal of epoxy resin due to the mismatches in thermal expansion between the interface bonding of rCF/epoxy. Based on the compression and wear test analysis, it was observed that the reinforcement effect of rCF-T has improved the compressive strength (4.09 %) and significantly enhanced the wear resistance (32.2 % at 1.0 m/s and 16 N) of epoxy composites as compared to rCF-AR which may attribute to the improved adhesion between the treated rCFs and epoxy matrix. Moreover, further improvement can be seen in EP/rCF-T/CNT as compared to EP/rCF-T for compressive strength (6.18 %) and wear resistance (16.4 % at 1.0 m/s and 16 N). This is because the addition of nano-size CNT in the composite has enhanced the local stress transferred by the matrix and the good reinforcing capability of CNT promotes better adhesion at the polymer matrix interface. From the study, it was clearly shown that the treated rCF was effective in improving the properties of the epoxy composites. Therefore, the treated rCF are valuable product worth to be considered as reinforcements in the composite materials. In addition, nanofillers serve as matrix reinforcement even at low filler content.